PENGARUH PERSEPSI YANG BAIK ATAS SISTEM PERPAJAKAN, KESADARAN MEMBAYAR PAJAK, PEMAHAMAN TENTANG PERATURAN PERPAJAKAN DAN KUALITAS PELAYANAN TERHADAP KEMAUAN MEMBAYAR PAJAK (Studi Empiris pada Wajib Pajak Orang Pribadi yang Melakukan Pekerjaan Bebas yang T - Sormin, Esra Aprilya; ', Zirman; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aimed to examine the effect of the good perception of the taxation system, pay taxes awareness, the understanding of tax regulation and quality of service through the awareness of paying taxes. This research applied a survey method and its population is whole of the individual taxpayer is registered in the primary tax office Dumai. the sampling technique using purposive sampling method and determination of sampel size in this study was calculated by formula slovin obtained by 100 respondents. The data of this research using primary data directly through a questionnaires and analyzed using spss 20. The data were analyzed to test the hypothesis using multiple linear regression analsys approach. The result of this study showed that the effect of good perception of the taxation system, pay taxes awareness, the understanding of tax regulation and quality of service have effect on willingness to pay taxes.Keywords: good perception, pay taxes awareness, tax regulation, quality of service and awareness of paying taxes.